Stratégies d'adaptation des producteurs agricoles aux risques hydroclimatiques dans le bassin Béninois de la pendjari à l'exutoire de Porga - P. Ouassa (Copernicus Publications, 2021)
West Africa's dependence on the increased impacts of extreme hydroclimatic hazards increases the vulnerability of food production to the resulting risks. This study analyses the adaptation strategies developed by agricultural producers in the Beninese Pendjari basin to cope with hydroclimatic risks. The methodological approach adopted consisted in the use of climatological data (height of daily and monthly rainfall) from the Tanguiéta and Natitingou stations over the period from 1965 to 2017 obtained in Météo-Bénin . Hydrological data consisting of the daily flows of the river calculation of the Pendjari indices at the Porga outlet, over the period 1965–2017 are extracted from the database of DG-Water and ltulization of socio-anthropological data. To better appreciate the adaptation strategies developed, a semi-structured survey that involved 121 people in 21 villages of the Beninese Pendjari basin is conducted according to the CAP approach (Knowledge, Attitudes, Practices). Direct observations in the field have also made it possible to better identify peasant adaptation strategies to the effects of hydroclimatic risks in the Beninese Pendjari basin. The information collected during the surveys was processed with Sphinx software. We studied socio-anthropological data, and we showed that Pendjari watershed in Benin is under the threat of hydroclimatic risks. To reduce their vulnerability, producers in the Benin Pendjari basin are developing several risk prevention and disaster management strategies. These include transplanting crops including sorghum by 100 % of the producers met, the disposal of logs, the enhancement of the shallows. In view of the effectiveness of the strategies identified and the limitations they present, it is important that the authorities develop a policy that is more sensitive to hydroclimatic risks, in order to improve the adaptation capacity of agricultural producers.